The Effect Of Motivation and Workload On Employee Performance By Mediating Organizational Commitment To The Blitar City Regional Secretariat - Siti Arifah; Ernani Hadiyati; Umi Muawanah (Publikasi Indonesia, 2023)
This research aims to analyse and prove the effect of work motivation on performance, work motivation on organisational commitment, workload on employee performance, workload on organisational commitment, organisational commitment on employee performance, work motivation on employee performance through organisational commitment and workload on performance employees through organisational commitment. The type of research used is explanatory research. Data collection used a questionnaire method, while the statistical analysis method used was PLS-SEM. The results of the research are that work motivation affects employee performance; work motivation does not affect organisational commitment; the workload does not affect employee performance; the workload affects organisational commitment, organisational commitment affects employee performance, organisational commitment has no effect in mediating work motivation on employee performance, organisational commitment influences mediating the influence of workload on employee performance.